Complete response in a patient with stage IV adrenocortical carcinoma treated with adjuvant trans‐catheter arterial chemo‐embolization (TACE). Issue 3 (6th September 2017) - Wong, Eugene; Jacques, Sarah; Bennett, Michael; Gorolay, Vineet; Lee, Adrian; Clarke, Stephen
Abstract: Adrenocortical carcinoma is a rare cancer, with estimate population incidence of 0.7–2.0 cases per 1 million each year. It also carries poor prognosis with estimated 5‐year survival of less than 15% of those with metastatic disease and has a poor response to cytotoxic treatment. A randomized controlled trial published in 2012 by Fassnacht et al . demonstrated improved progression‐free survival with first‐line etoposide‐doxirubicin‐cisplatin‐mitotane (EDP‐M) compared to first‐line streptozocin–mitotane in patients with stage III–IV disease. We report a case of a 25‐year‐old female diagnosed with adrenocortical carcinoma with liver and lung metastases treated with adjuvant EDP‐M chemotherapy. During her treatment, the patient experienced ongoing significant liver‐associated burden of disease, which prompted a trial of trans‐hepatic arterial chemoembolization with doxorubicin and mitomycin. The patient subsequently experienced complete remission of disease at 18 months with no fludeoxyglucose (FDG) avid lesions on PET/CT.